2018
DOI: 10.15406/freij.2018.02.00043
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide: sometimes it is a cooling gas, sometimes a warming gas

Abstract: The laws of physics, namely the gas laws, were applied to the gases in the atmosphere that act as ideal gases. The results show that as air temperature increases from winter to summer CO 2 is a cooling gas and from summer to winter it is a warming gas regardless of its concentration in the atmosphere. This is contrary to the commonly held belief that CO 2 always warms the atmosphere. Back radiation is the sum of the radiation of all of the greenhouse gases back to the Earth. It is a measured value and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many scholars [15,16,17,18,19,20] have claimed that global warming and climate change are associated with the amount of greenhouse gas emissions as measured by carbon dioxide equivalence. However, the literature also showed that there is no global consensus on this claim [21,22]. A report [23] mentioned that most of the leading scientific organizations around the world have issued public statements that endorse a position that 'climate warming trends over the past century are extremely likely due to human activities', and that the majority of actively publishing climate scientists (97%) agree that humans are causing climate change and global warming [24].…”
Section: Challenges To the Claims On The Causes Of Global Warming And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars [15,16,17,18,19,20] have claimed that global warming and climate change are associated with the amount of greenhouse gas emissions as measured by carbon dioxide equivalence. However, the literature also showed that there is no global consensus on this claim [21,22]. A report [23] mentioned that most of the leading scientific organizations around the world have issued public statements that endorse a position that 'climate warming trends over the past century are extremely likely due to human activities', and that the majority of actively publishing climate scientists (97%) agree that humans are causing climate change and global warming [24].…”
Section: Challenges To the Claims On The Causes Of Global Warming And...mentioning
confidence: 99%
“…While there is a lot of planning and efforts to develop mitigation strategies against the potential impacts of the increase in greenhouse gas emissions, it will be good to see good efforts in the development of mitigation and adaptation strategies for the potential impacts of 'naturalclimate-forcing'. Some scholars [21] applied the laws of physics (gas laws) to the gases in the atmosphere that act as ideal gases. The study reported that regardless of its concentration in the atmosphere, CO2 is a cooling gas as the air temperature increases from winter to summer while CO2 is a warming gas as air temperature changes from summer to winter.…”
Section: Challenges To the Claims On The Causes Of Global Warming And...mentioning
confidence: 99%